Function and Representation of Slang Word in Film “Mid90s” (2018): A Synchronic Approach: English - Widiya Apriliani; Ruminda; Erlan Aditya Ardiansyah (Journal of English Development, 2025)
This research aims to analyze the use of slang words in Jonah Hill's Mid90s (2018) through a synchronic approach. By adopting Allan and Burridge's (2006) theory of slang categories, Partridge's (2006) classification of slang functions, and Watt's (1984) paradigm of slang representation, this study identifies different types of slang used in the Movie's dialog. It explores their functions in marking teenage identity. Qualitative analysis of the dialog data revealed four main categories of slang: fresh and creative, imitative, flippant, and clipping. The findings also identified three main functions of slang in the movie: society slang, solidarity slang, and trade slang. Further analysis shows how the characters' use of slang reflects and reinforces social dynamics and group identity in skateboarding culture. This research contributes to sociolinguistics by providing a new perspective on the representation of language variation as a marker of youth identity in the era.